2007
DOI: 10.1007/s00508-006-0702-2
|View full text |Cite
|
Sign up to set email alerts
|

Learning by doing: a novel approach to improving general practitioners' diagnostic skills for common mental disorders

Abstract: The format chosen was successful in its intended educational endpoints. According to participants TRIPS is appropriate for the family practice situation and is accepted by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…However, some studies have shown that validation of these educational priorities for other team members by directly surveying them may be important as there is some evidence that psychiatrist perspectives on the training needs of primary care providers do not always align with the other primary care team members' perspectives [21,22]. In addition to discussing the learning priorities for the different members of the integrated care team, resident training programs may need to consider more formal didactic training in how to deliver education that is effectively integrated into clinical consultation.…”
Section: Clinical Educator For Integrated Carementioning
confidence: 97%
“…However, some studies have shown that validation of these educational priorities for other team members by directly surveying them may be important as there is some evidence that psychiatrist perspectives on the training needs of primary care providers do not always align with the other primary care team members' perspectives [21,22]. In addition to discussing the learning priorities for the different members of the integrated care team, resident training programs may need to consider more formal didactic training in how to deliver education that is effectively integrated into clinical consultation.…”
Section: Clinical Educator For Integrated Carementioning
confidence: 97%
“…A second option is to provide standardized questionnaires based on DSM or ICD (designated "instruments" in the following text) to support the consultation [15,59,60]. Such instruments are the subject for this thesis.…”
Section: Depression and Anxiety Disorders Are Treatablementioning
confidence: 99%
“…It is known that traditional continuing medical education programmes are not eff ective enough in behavioural change, i.e., improving counselling skills and in reducing and discontinuation of BZD [12]. Psychiatric training applying a short interview named Training for Interactive Psychiatric Screening (TRIPS) might help to improve physicians' diagnostic skills [21] and subsequently their prescription habits. Improved access to mental health workers and psychiatrists, being an international imperative in mental health [22], thus also applies for Slovenia.…”
Section: Discussionmentioning
confidence: 99%